Clinical outcomes following out-of-hospital cardiac arrest: The minute-by-minute impact of bystander cardiopulmonary resuscitation. (April 2023) - Cournoyer, Alexis; Grunau, Brian; Cheskes, Sheldon; Vaillancourt, Christian; Segal, Eli; de Montigny, Luc; de Champlain, François; Cavayas, Yiorgos Alexandros; Albert, Martin; Potter, Brian; Paquet, Jean; Lessard, Justine; et al.
Abstract: Aims: The time-dependent prognostic role of bystander cardiopulmonary resuscitation (CPR) for out-of-hospital cardiac arrest (OHCA) patients has not been described with great precision, especially for neurologic outcomes. Our objective was to assess the association between bystander CPR, emergency medical service (EMS) response time, and OHCA patients' outcomes. Methods: This cohort study used the Resuscitation Outcomes Consortium Cardiac Epidemiologic Registries. Bystander-witnessed adult OHCA treated by EMS were included. The primary outcome was survival to hospital discharge and secondary outcome was survival with a good neurologic outcome (modified Rankin scale 0–2). Multivariable logistic regression models were used to assess the associations and interactions between bystander CPR, EMS response time and clinical outcomes. Results: Out of 229, 637 patients, 41, 012 were included (18, 867 [46.0%] without bystander CPR and 22, 145 [54.0%] with bystander CPR). Bystander CPR was independently associated with higher survival (adjusted odds ratio [AOR] = 1.70 [95%CI 1.61–1.80]) and survival with a good neurologic outcome (AOR = 1.87 [95%CI 1.70–2.06]), while longer EMS response times were independently associated with lower survival to hospital discharge (each additional minute of EMS response time: AOR = 0.92 [95%CI 0.91–0.93], p < 0.001) and lower survival with a good neurologic outcome (AOR = 0.88 [95%CI 0.86–0.89], p < 0.001). There was no interaction between bystander CPR and EMS response time's association with survival (p = 0.12) and neurologic outcomes (p = 0.65). Conclusions: Although bystander CPR is associated with an immediate increase in odds of survival and of good neurologic outcome for OHCA patients, it does not influence the negative association between longer EMS response time and survival and good neurologic outcome.